Development and Mentoring of Catfish Cracker MSMEs Based on Andragogy Education in Sobo Village - Eka Danik Prahastiwi; Dian Tias Aorta (IMPACT: Journal of Innovation Mission and Community Service, 2025)
The development of Micro, Small, and Medium Enterprises (MSMEs) is an important strategy in empowering the economy of rural communities based on local potential. However, MSMEs in rural areas still face various obstacles, especially related to limited human resources, production skills, and business management capabilities. This community service activity aims to develop the catfish crackers MSME managed by the Rukun Makmur Joint Business Group (KUB) in Sobo Village through andragogy-based community education. The activity was carried out using a qualitative-descriptive approach with a participatory design. action The approach included needs identification, practice-based training, production assistance, and activity evaluation. The participants were 15 purposively selected MSMEs. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using thematic analysis. The results of the activity showed that the implementation of andragogy-based community education was able to encourage active participant involvement in all stages of production, increase understanding and technical skills, and improve product quality, characterized by more uniform cracker shape and thickness. However, some participants still experienced obstacles related to limited production facilities and time. Overall, this activity demonstrated that andragogy-based community education is effective as a model for developing and mentoring local food-based village MSMEs.